2009
DOI: 10.1088/1126-6708/2009/01/011
|View full text |Cite
|
Sign up to set email alerts
|

Unparticle signals with a few particles

Abstract: We use Padé approximants to systematically approximate scalar unparticle propagators and their associated phase factors by a finite number of ordinary particles. This is possible for conformal dimensions 1 ≤ d < 2, and also for d ≥ 2 if we add local terms. A small number of particles can, in some cases, mimic unparticle signals. We also discuss how the approximants capture basic unparticle properties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…To mimic a continuum, one can adjust the AdS curvature radius, R, such that R 1/M 5 and ∆m KK ≤ Γ H , the Higgs width. This is similar to a Padé approximation of the continuum [63].…”
Section: Jhep02(2020)026supporting
confidence: 57%
“…To mimic a continuum, one can adjust the AdS curvature radius, R, such that R 1/M 5 and ∆m KK ≤ Γ H , the Higgs width. This is similar to a Padé approximation of the continuum [63].…”
Section: Jhep02(2020)026supporting
confidence: 57%
“…There are other possibilities [11,24] for the structure of the above quadratic Lagrangian that correspond to differently shaped spectral density functions. The different shapes correspond to different ways in which the behavior of the theory makes the transition from the IR, where conformal symmetry is broken, to the UV, where it is restored.…”
Section: Generalized Free Field Theorymentioning
confidence: 99%
“…These include a composite Banks-Zaks particle with a continuum of masses [50][51][52], or alternatively a Sommerfeld-like model of massless fermions coupled to a massive vector field [53]. Recently, it was also shown that unparticlelike propagators may be mimicked by a small collection of ordinary particles via Padé approximations [54].…”
Section: Basics Of Unparticle Physicsmentioning
confidence: 99%